Betulin Inhibits Lung Metastasis by Inducing Cell Cycle Arrest, Autophagy, and Apoptosis of Metastatic Colorectal Cancer Cells - Han, Yo-Han (Nutrients, 2019)
Background: Colorectal cancer (CRC) is one of the diseases with high prevalence and mortality worldwide. In particular, metastatic CRC shows low probability of surgery and lacks proper treatment. In this study, we conducted experiments to investigate the inhibitory effect of betulin against metastatic CRC and related mechanisms. Methods: Water-soluble tetrazolium assay was used to determine the effect of betulin on metastatic CRC cell viability. Flow cytometry and TUNEL assay were performed to confirm whether betulin can induce apoptosis, autophagy, and cell cycle arrest. A lung metastasis mouse model was employed to estimate the anti-metastatic effect of betulin. Results: betulin decreased viability of metastatic CRC cells, including CT26, HCT116, and SW620 cell lines. Through PI3K/Akt/mTOR inactivation, betulin induced AMPK-mediated G0/G1 phase arrest and autophagy of CT26 and HCT116 cells. In addition, betulin occurred caspase-dependent apoptosis via the mitogen-activated protein kinase signaling pathway in metastatic CRC cells. Moreover, orally administered betulin significantly inhibited metastasis of CT26 cells to the lung. Conclusion: Our results demonstrate the anti-metastatic effect and therapeutic potential of betulin in metastatic CRC treatment.